Powassan virus: A tick borne flavivirus infecting humans - Xu Yang; George F. Gao; William J. Liu (Elsevier, 2022)
Infection of humans by Powassan virus (POWV) occurs rarely but is potentially life-threatening. First isolated in Ontario, Canada in 1958, the presence of POWV has been confirmed in three countries: Canada, the USA, and Russia. Although a limited number of human cases has been reported thus far, the infection rate has shown signs of increasing during the 21st century. Interestingly, POWV and a genetically close variant, deer tick virus (DTV), are the only member of the tick-borne flaviviruses known to be endemic in North America and maintain in respective tick-host cycles. In this review, we briefly summarize current knowledge involving the epidemiology and etiology, pathogenesis and immunity, molecular evolution, and protein functions of POWV, aiming to increase our understanding of the virus and unlock the potential to control this lethal pathogen. These data may also provide tools to minimize the future threat of other emerging and re-emerging viruses.